Considerations on the Controlled Delivery of Bioactive Compounds through Hyaluronic Acid Membrane - Eftimie Totu, Eugenia; Manuc, Daniela; Totu, Tiberiu; Marilena Cristache, Corina; Buga, Roxana-Madalina; Erci, Fatih; Cristea, Camelia; Isildak, Ibrahim (MDPI, 2022)
(1) Background: The standard treatment for periodontal disease, a chronic inflammatory state caused by the interaction between biofilms generated by organized oral bacteria and the local host defense response, consists of calculus and biofilm removal through mechanical debridement, associated with antimicrobial therapy that could be delivered either systemically or locally. The present study aimed to determine the effectiveness of a hyaluronic acid membrane matrix as a carrier for the controlled release of the active compounds of a formulation proposed as a topical treatment for periodontal disease, and the influence of pH on the complex system's stability. (2) Methods: The obtained hyaluronic acid (HA) hydrogel membrane with dispersed melatonin (MEL), metronidazole (MZ), and tetracycline (T) was completely characterized through FTIR, XRD, thermal analysis, UV-Vis and fluorescence spectroscopy, fluorescence microscopy, zeta potential and dielectric analysis. The MTT viability test was applied to check the cytotoxicity of the obtained membranes, while the microbiological assessment was performed against strains of Staphylococcus spp. and Streptococcus spp. The spectrophotometric investigations allowed to follow up the release profile from the HA matrix for MEL, MZ, and T present in the topical treatment considered. We studied the behavior of the active compounds against the pH of the generated environment, and the release profile of the bioactive formulation based on the specific comportment towards pH variation. The controlled delivery of the bioactive compounds using HA as a supportive matrix was modeled applying Korsmeyer-Peppas, Higuchi, first-order kinetic models, and a newly proposed pseudo-first-order kinetic model. (3) Results: It was observed that MZ and T were released at higher active concentrations than MEL when the pH was increased from 6.75, specific for patients with periodontitis, to a pH of 7.10, characterizing the healthy patients. Additionally, it was shown that for MZ, there is a burst delivery up to 2.40 x 10(-5) mol/L followed by a release decrease, while for MEL and T a short release plateau was recorded up to a concentration of 1.80 x 10(-5) mol/L for MEL and 0.90 x 10(-5) mol/L for T, followed by a continuous release; (4) Conclusions: The results are encouraging for the usage of the HA membrane matrix as releasing vehicle for the active components of the proposed topical treatment at a physiological pH.
Keywords: hyaluronic acid membrane; pH influence; melatonin; tetracycline; metronidazole; pH stability control; kinetic mechanism; PERIODONTAL-DISEASE; TOPICAL TREATMENT; DRUG-RELEASE; HYDROGEL; ANTIOXIDANT; METABOLISM; CHITOSAN; HEALTH; ANTIBIOTICS; Biochemistry & Molecular Biology; Chemistry; Engineering; Materials Science; Polymer Science